2019
DOI: 10.3390/medicina55070392
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Dyslipidaemia Using an Algorithm of Lipid Profile Measures among Newly Diagnosed Type II Diabetes Mellitus Patients: A Cross-Sectional Study at Dormaa Presbyterian Hospital, Ghana

Abstract: Background and Objectives: Dyslipidaemia and its associated complications have been reported to increase mortality among type 2 diabetes mellitus (T2DM) patients. However, there is a dearth of data on the incidence of dyslipidemia among Ghanaian patients with T2DM. This study evaluated dyslipidemia among newly diagnosed T2DM patients at Dormaa Presbyterian Hospital, Ghana. Materials and Methods: This cross-sectional study recruited a total of 215 participants at the Presbyterian Hospital, Dormaa-Ghana. A well-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 70 publications
(72 reference statements)
1
8
0
Order By: Relevance
“…In our study, the frequency of atherogenic dyslipidaemia, isolated dyslipidaemias and mixed dyslipidaemias was 10.5%, 58.09% and 53.33%, respectively ( Table 3 ). The pattern of dyslipidaemia observed in this study is consistent with results from different parts of Ghana [ 36 , 37 , 38 ], in Africa [ 4 ] and Asia [ 34 , 39 ]. The existence of atherogenic dyslipidaemia is linked to apolipoprotein B level, leading to a shift of the LDL pool toward small, dense, cholesterol-ester depleted LDL, believed to be more atherogenic and a higher risk for arteriosclerotic cardiovascular disease [ 40 , 41 ].…”
Section: Discussionsupporting
confidence: 91%
“…In our study, the frequency of atherogenic dyslipidaemia, isolated dyslipidaemias and mixed dyslipidaemias was 10.5%, 58.09% and 53.33%, respectively ( Table 3 ). The pattern of dyslipidaemia observed in this study is consistent with results from different parts of Ghana [ 36 , 37 , 38 ], in Africa [ 4 ] and Asia [ 34 , 39 ]. The existence of atherogenic dyslipidaemia is linked to apolipoprotein B level, leading to a shift of the LDL pool toward small, dense, cholesterol-ester depleted LDL, believed to be more atherogenic and a higher risk for arteriosclerotic cardiovascular disease [ 40 , 41 ].…”
Section: Discussionsupporting
confidence: 91%
“…Dyslipidemia is a major risk factor for cardiovascular disease and stroke 25 . In Ghana, there is limited data on the prevalence of dyslipidemia among patients with diabetes 14,26 . Previous studies have shown that prevalence of dyslipidemia is associated with sociodemographic characteristics and lifestyle behaviors 27–29 .…”
Section: Discussionmentioning
confidence: 99%
“…The rise in the number of diabetes‐associated dyslipidemia cases is due to rapid urbanization and the adoption of western diet and lifestyle, 12,13 and this is gaining prominence in Ghana. A previous study conducted by Anto and colleagues among the Ghanaian population found that dyslipidemia was associated with obesity, sedentary lifestyle, socioeconomic status, and family history of diabetes 14 . Similarly, an Ethiopian study linked dyslipidemia among individuals with diabetes to factors such as age, gender, obesity, and the duration of living with the condition 15 …”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Billimek et al (2015) showed that females diagnosed with T2DM are less likely to achieve target goals for lipids, and also had a higher prevalence of dyslipidemia versus men [15]. Anto et al (2019) reported that dyslipidemia is more prevalent in diabetic males rather than females and that subjects aged 40 or elder are particularly affected by lipid disturbances [16]. In terms of CHD prevalence, Li et al (2017) described an 18.1% prevalence of CHD in diabetic males and 10.4% in diabetic females, and that CHD is found in 19.6% of the subjects aged ≥65 years versus 10.3% in the subjects aged 18 to 64 years.…”
Section: Discussionmentioning
confidence: 99%